Effect of previous desensitizer and rewetting agent application on shear bond strength of bonding - Soares, Carlos José; Santos Filho, Paulo César F.; Barreto, Bruno C. F.; Mota, Adérito S. (Brazilian Dental Science, 2010)
This study evaluated the effect of desensitizer and rewetting agent on dentin shear bond strength. One hundred thirty five bovine incisive teeth had their buccal surfaces ground down to produce a fl at superficial dentin surfaces and received the following treatments: G1- One Step Plus (OSP) and resin cylinder adhesive fi xation (RI); G2- Gluma One Bond (GOB) and RI; G3- Single Bond (SB) and RI; G4- Aqua-Prep (AP) + OSP and RI; G5- Gluma Desensitizer (GD) + GOB and RI; G6- GD + SB and RI; G7- GD + OSP and RI; G8- AP + GOB and RI; G9- AP + SB and RI. The specimens were stored at 37°C and 100% humidity for 24 hours and a shear bond test was performed with a mechanical testing machine, at a crosshead speed of 0.5 mm⁄min. The data were submitted to one-way ANOVA followed by the Tukey test (p<0.05). The results (MPa) were: G1: 10.75(2.64)a; G2: 10.28(2.58)a; G3: 11.63(4.59)a; G4: 10.93(4.88)a; G5: 10.15(3.95)a; G6: 11.82(4.14)a; G7: 9.85(2.15)a; G8: 5.48(1.94)b; G9: 10.62(2.83)a. The resistance of the GOB adhesive system was negatively affected by AP application. The use of desensitizer and rewetting agent does not compromise the bond strength when they are compatible with the adhesive system used.